Human Destinies In Stories: Conflict And Psychologism - Suxrob Saitov Djumaydillayevich (Global Scientific Publishing, 2024)
In this article, conflictuality is a phenomenon related to psychologism, because it first appears in the human mind, and then it appears in the mood. In the writer's story "The Road Turns", “Yo‘l aylanib”, the episode that reflects Sam's inner-psychological conflict with himself is the culminating point. The essence of X.Sultan's story “Honor”, (Nomus), the interpretation of the fate of the heroes, and the impact of O. Henry's story (the true health center) “Haqiqiy siyatgoh”, can be felt in terms of psychology and conflict. In the writer's stories “Bir tup xurmo”, (A bunch of dates) and “Do‘stim, Esonboy” (my friend, Esonboy), the conflict against the extortionists and extortionists served as the main force developing the plot
Keywords: Book of the Smokers; American Romantic Writers